PENGARUH KOMITMEN ORGANISASIONAL, JOB ENGAGEMENT DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. INFOMEDIA SOLUSI HUMANIKA - Ali Fani Mumtaza; Hadi Sunaryo; M Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This study aims to determine the effect of organizational commitment, job engagement and job satisfaction on the performance of employees of PT. Infomedia Humanika Solution. The variables used in this study are performance variables (dependent variables), while the independent variables are organizational commitment, job engagement and job satisfaction. The results of this study partially concluded that there was an influence between organizational commitment on employee performance, job engagement on performance and job satisfaction on employee performance. Simultaneously there is an influence between organizational commitment, job engagement and job satisfaction on employee performance. Keywords: Performance, Organizational Commitment, Job Involvement, Job Satisfaction.